Elements of inclusiveness in Science teaching to students with intellectual disabilities: a literature review (Research, Society and Development, 2021)
In order to meet the needs of an inclusive pedagogical practice in Science Education, this study aims to identify elements of inclusiveness such as curriculum flexibility in science education for students with intellectual disabilities. For this purpose, the bibliographical review of Brazilian scientific productions in articles, course completion work, theses and dissertations published in the last five years is used as research methodology. The analysis of the data obtained evidenced the need for the continuing education of the teacher for the insertion of these elements in his planning, contemplating the use of assistive technologies, playful activities, the CTSA approach that favors the development of critical thinking as well as a basis to discuss the relationships between knowledge and curriculum in an inclusive context.